Quality antenatal care services delivery at health facilities of Ethiopia, assessment of the structure/input of care setting - Atkure Defar; Theodros Getachew; Girum Taye; Tefera Tadele; Misrak Getnet; Tigist Shumet; Gebeyaw Molla; Geremew Gonfa; Habtamu Teklie; Ambaye Tadesse; Abebe Bekele (BMC, 2020)
Abstract Background According to the Donabedian model, the assessment for the quality of care includes three dimensions. These are structure, process, and outcome. Therefore, the present study aimed at assessing the structural quality of Antenatal care (ANC) service provision in Ethiopian health facilities. Methods Data were obtained from the 2018 Ethiopian Service Availability and Readiness Assessment (SARA) survey. The SARA was a cross-sectional facility-based assessment conducted to capture health facility service availability and readiness in Ethiopia. A total of 764 health facilities were sampled in the 9 regions and 2 city administrations of the country. The availability of equipment, supplies, medicine, health worker's training and availability of guidelines were assessed. Data were collected from October-December 2017. We run a multiple linear regression model to identify predictors of health facility readiness for Antenatal care service. The level of significance was determined at a p-value < 0.05. Result Among the selected health facilities, 80.5% of them offered Antenatal care service. However, the availability of specific services was very low. The availability of tetanus toxoid vaccination, folic acid, iron supplementation, and monitoring of hypertension disorder was, 67.7, 65.6, 68.6, and 75.1%, respectively. The overall mean availability among the ten tracer items that are necessary to provide quality Antenatal care services was 50%. In the multiple linear regression model, health centers, health posts and clinics scored lower Antenatal care service readiness compared to hospitals. The overall readiness index score was lower for private health facilities (β = − 0.047, 95% CI: (− 0.1, − 0.004). The readiness score had no association with the facility settings (Urban/Rural) (p-value > 0.05). Facilities in six regions except Dire Dawa had (β = 0.067, 95% CI: (0.004, 0.129) lower readiness score than facilities in Tigray region (p-value < 0.015). Conclusion This analysis provides evidence of the gaps in structural readiness of health facilities to provide quality Antenatal care services. Key and essential supplies for quality Antenatal care service provision were missed in many of the health facilities. Guaranteeing properly equipped and staffed facilities shall be a target to improve the quality of Antenatal care services provision.